Eating Disorders Spectrum During the COVID Pandemic: A Systematic Review - Miniati, Mario; Marzetti, Francesca; Palagini, Laura; Marazziti, Donatella; Orrù, Graziella; Conversano, Ciro; Gemignani, Angelo (Frontiers in Psychology, 2021)
Background: Several data suggest that COVID-19 pandemic might exacerbate or trigger Eating Disorders (EDs). The aim of this paper was to summarize present literature on COVID pandemic and EDs. Methods: Literature search, study selection, methods, and quality evaluation were performed following PRISMA Guidelines. Results: The systematic search permitted the identification of 91 studies; 21 papers were eligible and included in the review. Nine papers (42.9%) evaluated the effect of pandemic and associated protective and risk factors in EDs patients, ten (47.6%) explored the prevalence of disturbed eating behaviours and risk factors for exacerbating EDs in the general population, and the remaining two (9.5%) were qualitative studies describing the impact of lockdown and quarantine on EDs patients. Their analysis revealed five main findings: 1) changes in physical activities routines were related to a worsening of preoccupation on weight/body shape; 2) food access limitation during pandemic represented a risk factors for both triggering and exacerbating EDs; 3) restriction in healthcare facilities contributed to increase anxiety levels and modifies treatment compliance; 4) social isolation was related to symptoms’ exacerbation in EDs patients who are home-confined with family members; 5) conflicts and difficulties in relationships with ‘no way out’ were maintenance factors for EDs symptoms, especially in adolescents and young adults. Conclusion: COVID-19 pandemic had a negative impact on EDs that might be triggered or worsened by the exceptional conditions deriving from COVID-19-related stress in predisposed subjects. Patients already affected by EDs experienced a worsening of their clinical conditions and related quality of life.